miR-483 Targeting of CTGF Suppresses Endothelial-to-Mesenchymal Transition: Therapeutic Implications in Kawasaki Disease - He, Ming; Chen, Zhen; Martin, Marcy; Zhang, Jin; Sangwung, Panjamaporn; Woo, Brian; Tremoulet, Adriana H.; Shimizu, Chisato; Jain, Mukesh K.; Burns, Jane C.; Shyy, John Y.-J. (Circulation research, 2017)
RATIONALE:Endothelial–mesenchymal transition (EndoMT) is implicated in myofibroblast-like cell–mediated damage to the coronary arterial wall in acute Kawasaki disease (KD) patients, as evidenced by positive staining for connective tissue growth factor (CTGF) and EndoMT markers in KD autopsy tissues. However, little is known about the molecular basis of EndoMT involved in KD. OBJECTIVE:We investigated the microRNA (miRNA) regulation of CTGF and the consequent EndoMT in KD pathogenesis. As well, the modulation of this process by statin therapy was studied. METHODS AND RESULTS:Sera from healthy children and KD subjects were incubated with human umbilical vein endothelial cells. Cardiovascular disease–related miRNAs, CTGF, and EndoMT markers were quantified using reverse transcriptase quantitative polymerase chain reaction, ELISA, and Western blotting. Compared with healthy controls, human umbilical vein endothelial cell incubated with sera from acute KD patients had decreased miR-483, increased CTGF, and increased EndoMT markers. Bioinformatics analysis followed by functional validation demonstrated that Krüppel-like factor 4 (KLF4) transactivates miR-483, which in turn targets the 3′ untranslated region of CTGF mRNA. Overexpression of KLF4 or pre-miR-483 suppressed, whereas knockdown of KLF4 or anti-miR-483 enhanced, CTGF expression in endothelial cells in vitro and in vivo. Furthermore, atorvastatin, currently being tested in a phase I/IIa clinical trial in KD children, induced KLF4-miR-483, which suppressed CTGF and EndoMT in endothelial cells. CONCLUSIONS:KD sera suppress the KLF4-miR-483 axis in endothelial cells, leading to increased expression of CTGF and induction of EndoMT. This detrimental process in the endothelium may contribute to coronary artery abnormalities in KD patients. Statin therapy may benefit acute KD patients, in part, through the restoration of KLF4-miR-483 expression. CLINICAL TRIAL REGISTRATION:URLhttp://www.clinicaltrials.gov. Unique identifierNCT01431105.